Cognitive Substrate of Linguistic Thinking: The Semiotic Aspect - Ekaterina V. Savitskaya; Vladimir M. Savitskij (Publishing house "Sreda", 2020)
The article is devoted to a description of cognitive attitude complexes that underlie linguistic thinking and function in the form of cultural codes. Such complexes form a cognitive substrate of linguistic thinking. It has ethnocultural and ethnolinguistic specificity. Research methods: analysis, comparison, descriptive method, interlinguistic comparison of mercantilist and military cultural codes on the basis of English and Russian linguocultural materials. Research results. It is outlined that the cognitive substrate of the linguistic thinking performs the function of modelling reality, acting as a complex of cultural codes. It is shown that the codes used by a person in his / her linguistic thinking are divided into internal and external ones. Internal codes are spiritually close to their user; he / she forms thoughts in them, and as for external codes, he / she only verbally formulates thoughts, translates them from internal to external code. Among the internal codes, there is a cultural code that is closest to the person because of his / her state, occupation, etc. It is concluded that the person views the surrounding world through the prism of the most familiar sphere of life, making it a model of the world and a cultural code.